Pengaruh Layanan Koperasi Unit Desa terhadap Penerimaan Petani Kelapa Sawit (Suatu Kasus di Koperasi Unit Desa Karya Jaya, Desa Bukit Harapan, Kecamatan Merlung, Kabupaten Tanjung Jabung Barat, Provinsi Jambi) - Puteri, Yuni Indriyana; Karyani, Tuti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Village Unit Cooperatives (KUD), particularly KUD Karya Jaya, play a role as institutions that support the economic activities of oil palm farmers in Bukit Harapan Village, Merlung, Jambi Province. However, the business performance and service quality of KUD Karya Jaya are experiencing a downward, potentially affecting the revenue of oil palm farmers in the village. This study aims to analyze the influence of fresh fruit bunch (FFB) marketing services, savings and loan services, and production facilities services on the revenue of oil palm farmers in Bukit Harapan Village, Merlung, Jambi Province. The analysis method used is multiple linear regression, with data transformed using the Method of Successive Interval (MSI). Data were collected from 84 active members of KUD Karya Jaya using simple random sampling. The results show that FFB marketing services, savings and loan services, and production facilities services simultaneously have a significant effect on revenue, with an adjusted R square value of 0.307. This indicates that these three services simultaneously explain 30,7% of the variation in the revenue of oil palm farmers who are members of KUD Karya Jaya, while the remaining 69,3% is explained by other factors outside the model not examined in this study. Partially, each of these services also has a significant effect on the revenue of oil palm farmers.